Impact of Personal Cooling on Performance, Comfort and Heat Strain of Healthcare Workers in PPE, a Study From West Africa - Bonell, Ana; Nadjm, Behzad; Samateh, Tida; Badjie, Jainaba; Perry-Thomas, Robyn; Forrest, Karen; Prentice, Andrew M.; Maxwell, Neil S. (Frontiers in Public Health, 2021)
Background: Personal protective equipment (PPE) is an essential component of safely treating suspected or confirmed SARS-CoV-2 patients. PPE acts as a barrier to heat loss, therefore increasing the risk of thermal strain which may impact on cognitive function. Healthcare workers (HCWs) need to be able to prioritize and execute complex tasks effectively to ensure patient safety. This study evaluated pre-cooling and per-cooling methods on thermal strain, thermal comfort and cognitive function during simulated emergency management of an acutely unwell patient. Methods: This randomized controlled crossover trial was run at the Clinical Services Department of the Medical Research Unit The Gambia. Each participant attended two sessions (Cool and Control) in standard PPE. Cool involved pre-cooling with an ice slurry ingestion and per-cooling by wearing an ice-vest external to PPE. Results: Twelve participants completed both sessions. There was a significant increase in tympanic temperature in Control sessions at both 1 and 2 h in PPE (p = 0.01). No significant increase was seen during Cool. Effect estimate of Cool was −0.2°C (95% CI −0.43; 0.01, p = 0.06) post 1 h and −0.28°C (95% CI −0.57; 0.02, p = 0.06) post 2 h on tympanic temperature. Cool improved thermal comfort (p < 0.001), thermal sensation (p < 0.001), and thirst (p = 0.04). No difference on cognitive function was demonstrated using multilevel modeling. Discussion: Thermal strain in HCWs wearing PPE can be safely reduced using pre- and per-cooling methods external to PPE.